Advertising and Sales Performance of Selected Companies in Mogadishu- Somalia (Global Journal of Management and Business Research, 2024)
This study investigated the causal relationship between advertising and sales performance in selected companies in Mogadishu Somalia. Since advertising is applied in order to raise awareness among customers. Thus, it could maintain customer loyalty and then boost up the organization performance in terms of profitability of the organization and its value. However, it is not certain whether adverting can increase organization performance in Mogadishu Somalia because the cost may be too high for the organization to sustain it, thus it may have adverse effects on organizational performance. The specific objectives of this study were as follows: To examine how media advertising, Celebrity Advertising, Billboard Advertising affect sales performance in some selected companies in Mogadishu-Somalia. This study was guided by the theory of advertising promotions, advanced by Smith and Taylor (2003). The theory postulates that advertising promotions involve high costs and, hence, companies are always looking for ways to reduce the cost of promotions but still maintain the effectiveness of the promotional activities being carried out. This is where companies use joint promotions. This study employed a descriptive correlational and a cross sectional survey design. Therefore, the descriptive design enabled the researcher to determine the picture or document current conditions or attitudes to describe the effect of advertisement and sales performance of the selected companies in Mogadishu Somalia.